Fear of Evaluation and Online Self-Disclosure on WeChat: Moderating Effects of Protective Face Orientation - Zeng, Runxi; Zhu, Di (Frontiers in Psychology, 2021)
Fear of evaluation is a key factor that affects how social media users present themselves to others, but little is known about the effects and mechanisms involved, especially on the relationship between fear of positive evaluation and online self-disclosure. This study explores how fear of evaluation affects online self-disclosure and examines how this relationship is moderated by protective face orientation in the Chinese context. A total of 750 Chinese WeChat users constituted the sample for a questionnaire-based analysis and regression analysis. The results showed that both fear of positive evaluation and fear of negative evaluation had a significant negative effect on the amount of online self-disclosure and a significant positive effect on the depth of online self-disclosure. Protective face orientation had a moderating effect on the relationship between fear of evaluation and online self-disclosure for both the amount and depth of online self-disclosure. Our findings suggest that social network site (SNS) users' fear of evaluation can be attributed to their cognitive attitude toward the external environment, and the loss of face in the Chinese context can be included in the social context.